Market access through bound tariffs - Davide Sala; Philipp J. H. Schröder; Erdal Yalcin (Center for Economic Studies and ifo Institute (CESifo), 2009)
WTO negotiations deal predominantly with bound - besides applied - tariff rates. But, how can reductions in tariffs ceilings, i.e. tariff rates that no exporter may ever actually be confronted with, generate market access? The answer to this question relates to the effects of tariff bindings on the risk that exporters face in destination markets. The present paper formalizes the underlying interaction of risk, fixed export costs and firms' market entry decisions based on techniques known from the real options literature; doing so we highlight the important role of bound tariffs at the extensive margin of trade. We find that bound tariffs are more effective with higher risk destination markets, that a large binding overhang may still command substantial market access, and that reductions in bound tariffs generate effective market access even when bound rates are above current and long-term applied rates.
Keywords: F12; F13; F15; 330; bound tariffs; Doha Round; WTO; heterogeneous firms; entry; dynamics; tariff bindings; Zolltarif; Selbstverpflichtung; Zollpolitik; Außenhandelsliberalisierung; WTO-Regeln; Wirkungsanalyse; Exportindustrie; Markteintritt; Entscheidung; Realoption; Theorie